COVID-19 among migrants, refugees, and internally displaced persons: systematic review, meta-analysis and qualitative synthesis of the global empirical literature - Hintermeier, Maren; Gottlieb, Nora; Rohleder, Sven; Oppenberg, Jan; Baroudi, Mazen; Pernitez-Agan, Sweetmavourneen; Lopez, Janice; Flores, Sergio; Mohsenpour, Amir; Wickramage, Kolitha; Bozorgmehr, Kayvan (EClinicalMedicine, 2024)
Background - Evidence amounted early that migrants, who are often side-lined in pandemic response or preparedness plans, are disproportionately affected by the COVID-19 pandemic and its consequences. However, synthesised evidence that quantifies the magnitude of inequalities in infection risk, disease outcomes, consequences of pandemic measures or that explains the underlying mechanisms is lacking. - Methods - We conducted a systematic review searching 25 databases and grey literature (12/2019 to 09/2023) and considered empirical articles covering migrants, refugees, asylum-seekers, and internally displaced persons reporting COVID-19 cases, hospitalisation, ICU admission, mortality, COVID-19 vaccination rates or health consequences of pandemic measures. Random-effects meta-analysis of observational studies and qualitative analysis were performed for evidence synthesis. A protocol was registered with PROSPERO (CRD42021296952). - Findings - Out of 17,088 records, we included 370 reports in the review. For the quantitative studies (n = 65; mainly from high income countries), meta-analysis with over 53 million participants studied showed that, compared to non-migrants, migrants have an elevated risk of infection (RR = 1.84; 95%-CI: 1.44-2.35) but similar risk for hospitalisation (RR = 1.10; 0.91-1.33), while the probability of ICU admission was higher (RR = 1.23; 0.99-1.52). Among those hospitalised, migrants had a lower risk of mortality (RR = 0.56; 0.42-0.76), while their population-based mortality tended to be higher (RR = 1.46; 0.95-2.26). The qualitative synthesis (n = 75) highlighted the complex interplay of social and COVID-19-related factors at different levels. This involved increased exposure, risk, and impact of pandemic measures that compromised the health of migrants. - Interpretation - Even in the advanced stages of the pandemic, migrants faced higher infection risks and disproportionately suffered from the consequences of COVID-19 disease, including deaths. Population-level interventions in future health emergencies must better consider socio-economic, structural and community-level exposures to mitigate risks among migrants. Enhancing health information systems is crucial, as the lack of migration variables makes it difficult to close coverage gaps, leaving migrants largely ‘invisible’ in official data. - Funding - None.